Festival Anak Sholeh Sebagai Media Edukasi Ukhuwah Islamiyah Di Masyarakat Desa Pasir Permit Kec.Lima Puluh Kab. Batu Bara - Putri Annisa Purba; Mara Samin Lubis; Chandra Anggi Pradana (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Students from UINSU KKN organize the Sholeh Children's Festival with the goal of teaching religious moderation in society. Through a variety of imaginative and engaging exercises, this activity encourages kids to understand the virtues of harmony, tolerance, and respect for one another. It is believed that by promoting a greater knowledge of religious moderation through this celebration, the likelihood of societal unrest will be decreased. Supporting this education also requires the community's and parents' involvement. It is therefore hoped that the Sholeh Children's Festival would serve as a springboard for creating a society that is more accepting and peaceful.